Market Opportunities and New Sheep Meat Products Produced by Sustainable Farming System - Teixeira, Alfredo; Rodrigues, Sandra; Cabo, Paula; Castro, José; Castro, Marina (European Journal of Applied Sciences, 2023)
Within the scope of the Open preserve project in northern Portugal, an integrated assessment has been developed to evaluate the efficiency of pyric herbivory to maintain open landscapes and the farm products' quality of livestock products using it. As a measurement of farm system evaluation, some meat products quality was analysed, particularly meat lamb and some meat processed products as hamburgers, sausages, pâtés, and cured legs from carcasses that come out of PGI or PDO quality brands. Results indicated that lambs produced were in the quality requirements of similar products produced in the region. The processed products would be an interesting alternative for the meat industry and a novelty for consumers, adding value to carcasses with low commercial price and consumer reduced acceptability